Tipe Kepribadian pada Pasien Hipertensi - I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2017)
This study aims to determine the personality of hypertensive patients in the work area of Tabanan III Puskesmas in 2017. The type of this research is descriptive research, using Cross Sectional approach. The sampling technique is Consecutive sampling, with the total sample of 59 people. Data collection using Type A and Type B Behavior Patterns. The results showed that most personality types in hypertensive patients were A personality type of 33 people (55.9%). Most personality types A have a history of hypertensive offspring that is as many as 25 people (75.8%), and living in the environmental temperature as many as 28 people (84.8%).